Mycobacteriosis outbreak caused by Mycobacterium aviumsubsp.avium detected through meat inspection in five porcine fattening farms - Pérez de Val, B.; Grau-Roma, Llorenc; Segalés, J.; Domingo, M.; Vidal, E. (BMJ Publishing Group, 2013)
Between December 2010 and January 2011 a number (n=20) of cases were submitted to the Slaughterhouse Support Service (Servei de Suport a Escorxadors, SESC-CReSA), consisting of grossly nodular granulomatous and caseous lesions in pig carcasses from five different farms. Lesions involved lymph nodes, lungs, liver and spleen.